Sosialisasi Pembuatan Bio Solar menggunakan Minyak Jelantah dan Menciptakan Lingkungan yang Bersih dilingkungan RW019 Desa Kedung Pengawas Kabupaten Bekasi - Muhendra, Rifki; Nuraliyah, Andi; Aryafangger, Thomas Romyansen; Davi, Faradilla Aulia; Ferdiansyah, Ikhsan; Prakoso, Endah Ningrat Jati; Nugroho, Ricko Puspo; Alrasyid, Muhamad Aji Maulana; Amin, Abu Ridho Al; Perdiansyah; Putra, Achmad Mandala; P, Diovan Dharma; Spalanzani, Widya (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
The Real Work Lecture Program carried out by Group 2 has the aim of utilizing used cooking oil to make biodiesel which has been recognized as an effective step in reducing the negative impact of used cooking oil waste on the environment. This service aims to socialize the process of making biodiesel from used cooking oil to the public, with a focus on environmental sustainability. Socialization methods are carried out through public campaigns, practical training, and providing information regarding the environmental benefits of using biodiesel. The results of this outreach show an increase in public awareness of the potential of biodiesel as an environmentally friendly and economical alternative. The implication of this service is to create a clean environmentthrough more effective management of used cooking oil, supporting global efforts to reduce the carbon footprint, as well asincreasing energy independence at the local level. It is hoped that these results can make a positive contribution to the implementationof renewable energy policies in the future. The main focus is to increase public awareness of the importance of maintaining a clean environment and its positive impact on health and quality of life. The results of this outreach show increased participation in cleaning activities, better waste management, and efficient use of resources. The implication of this research is to support globalefforts to maintain environmental sustainability and promote environmentally friendly lifestyles.